Pharmacognosy Study And Quality Control Study Of Gomutra Of Icg (India Cow Gomutra) And Jcg (Jersey Cow Gomutra) - kato, Anu Tatak; Murthy, A Rama; Joshi, Krutika; Sharma, Gaurav (International Research Journal of Ayurveda & Yoga, 2020)
Our great Acharyas believed in Serendipity which lead to discovery of gomutra as a dravya, in Ayurveda. As since ancient times the Religion and science have co existed so, there was wide practice as parallel treatment of medical science with religion, thereby considering the cow (Kamadhenu) worth worshiping, the milk and urine. Acharyas have prescribed the treatment for various diseases where Gomutra is used a medicine to cure various diseases causing elements. All the bhirhat triya and lagutriya had mentioned the properties, formulations and use of it in various vayadhi specially udharoga chikitsha and ghraha dosha treatment, as it considered as pious in Hindu religion.